Preclinical evaluation of the immunogenicity and safety of an inactivated enterovirus 71 candidate vaccine. - Shi-Hsia Hwa; Yock Ann Lee; Joseph N Brewoo; Charalambos D Partidos; Jorge E Osorio; Joseph D Santangelo (PLoS Neglected Tropical Diseases)
Human enterovirus 71 (EV71) is a significant cause of morbidity and mortality from Hand, Foot and Mouth Disease (HFMD) and neurological complications, particularly in young children in the Asia-Pacific region. There are no vaccines or antiviral therapies currently available for prevention or treatment of HFMD caused by EV71. Therefore, the development of therapeutic and preventive strategies against HFMD is of growing importance. We report the immunogenic and safety profile of inactivated, purified EV71 preparations formulated with aluminum hydroxide adjuvant in preclinical studies in mice and rabbits. In mice, the candidate vaccine formulations elicited high neutralizing antibody responses. A toxicology study of the vaccine formulations planned for human use performed in rabbits showed no vaccine-related pathological changes and all animals remained healthy. Based on these preclinical studies, Phase 1 clinical testing of the EV71 inactivated vaccine was initiated.